Regional Economic Resilience: European Experiences and Policy Issues - Wink, Rüdiger (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
This introductory paper looks at recent debates on the concept of regional economic resilience and focuses on three elements of debate: (1) indicator systems and consideration of the normative content of the concept; (2) the evolutionary dimension of the concept and its inter-disciplinary linkages; (3) the policy dimension and challenges for the development of policy recommendations. The author discusses the state of the debate and presents some directions for future research priorities.